Spectral bimodality of waves produced by hurricanes in the Caribbean coastal zone off Mexico - Raúl Martell-Dubois; Rodolfo Silva-Casarin; Edgar G Mendoza-Baldwin; Juan J Muñoz-Pérez; Sergio Cerdeira-Estrada; Edgar Escalante-Mancera; Irene Laiz (Ciencias Marinas, 2018)
Wave data collected near the Caribbean coast of Mexico were used to study the frequency and directional structure of the wave field that was generated during the passing of 3 hurricanes. The data were recorded with 2 different acoustic wave gauges, which were installed at a depth of about 20 m. These records provided 183 directional wave spectra corresponding to the occurrence of hurricanes Wilma (October 2005), Dean (August 2007) and Rina (October 2011). The simultaneity of wind waves and swell was detected from different directions, due to the presence of bimodal spectra. For the 3 events, the relation between the translational speed of hurricanes and wave group celerity can explain the presence or absence of spectral bimodality, in either frequency or direction.